A SYSTEMATIC REVIEW: DIGITAL LITERACY FOR STRENGTHENING CHARACTER IN FACING THE ERA OF SOCIETY 5.0 - Esty Setyo Utaminingsih; Ellianawati Ellianawati; Nuni Widiarti; Sri Sumartiningsih; Maria Ayu Puspita (Research and Development Journal of Education, 2023)
Era Society 5.0 is a concept to solve various social problems in the Industrial Revolution 4.0 era, such as a moral crisis and a decline in character values. Digital literacy is a solution to strengthen students' character values. This article aims to present information about the role of digital literacy in supporting character in the era of Society 5.0. The method used in this study was PRISMA (Preferred Items for Systematic Reviews and Meta-Analysis), which consisted of three steps: identification, screening, and inclusion. The number of articles found is 512 from 2018 to 2022. This study decided to review 17 items based on three systematic literature review analysis steps. The results showed that (1) the most frequently used method is the qualitative method with data collection techniques such as interviews, observation, and documentation, (2) technological capabilities and digital literacy competencies must be balanced, (3) schools need to apply digital literacy competencies to strengthen the value of the character to avoid negative impact from using technology to remain competitive in the international arena while remaining polite and of good character.